High-performance and high-concurrency encryption scheme for Hadoop platform - Wei JIN; Mingjie YU; Fenghua LI; Zhengkun YANG; Kui GENG (Tongxin xuebao)
To address the problem that as preventing data leakage on Hadoop platform,the existing encryption schemes suffer from several problems (e.g.,single encryption algorithm,complicated key management,low encryption performance) and they cannot protect data stored in Hadoop effectively,a high-performance encryption and key management scheme for Hadoop was proposed.Firstly,a three-level key management system was extended with the domestic commercial cipher algorithm.Then,a new data structure for encryption zone key to reduce time consumption was designed.Finally,the computing process of data stream in parallel was scheduled.The experimental results show that compared with the existing Hadoop schemes,the proposed scheme can improve the efficiency of key management,and can speed up file encryption.